2016
DOI: 10.1136/thoraxjnl-2015-208026
|View full text |Cite
|
Sign up to set email alerts
|

TB in healthcare workers in the UK: a cohort analysis 2009–2013

Abstract: The lack of an increased risk of TB after stratifying by country of birth, and the very few transmission events involving nosocomial transmission in the UK suggests that TB in HCWs in the UK is not generally acquired through UK occupational exposure. The majority of cases in foreign-born HCWs are likely to result from reactivation of latent TB infection (LTBI) acquired abroad, and is not likely to be prevented by BCG vaccination in the UK. Testing and treatment of LTBI in HCWs with exposure to high TB burden c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…While nosocomial transmission of tuberculosis (TB) has been relatively uncommon in low TB-burden countries 2 , healthcare workers (HCWs) who routinely perform high-risk procedures such as bronchoscopy, are at increased risk of TB exposure 3 . In addition, international travel has facilitated TB outbreaks in health-care settings.…”
Section: Introductionmentioning
confidence: 99%
“…While nosocomial transmission of tuberculosis (TB) has been relatively uncommon in low TB-burden countries 2 , healthcare workers (HCWs) who routinely perform high-risk procedures such as bronchoscopy, are at increased risk of TB exposure 3 . In addition, international travel has facilitated TB outbreaks in health-care settings.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] DNA fingerprinting studies have shown that a substantial proportion of TB in HCWs in low-incidence countries is not a result of occupational exposure in healthcare settings in these countries. 12,13 In the United Kingdom, 85% of HCW TB cases were foreign born, and TB was presumably the result of an infection acquired before starting work in a UK healthcare institution; 13 the infection was likely acquired during healthcare work in the HCW's country of origin. In 3 years (2010-2012), only 10 events (3.3 per year) were identified involving patient-to-HCW transmission.…”
mentioning
confidence: 99%
“…15 Therefore, all HCWs from the Philippines should have received OH assessment. Between 2009 and 2013, 11% of HCWs with TB in the UK were born in the Philippines 5 which means targeted OH assessment could have a significant impact on preventing development of active TB disease in this population, and other high TB incidence countries, as well as ensuring early diagnosis and treatment. Indeed a recent study in the North of England identified a high proportion of LTBI among HCWs from high TB incidence countries, including the Philippines.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In low incidence countries, such as the UK, TB mainly affects nonnative born HCWs who originate from high TB incidence countries. 5 Despite the considerable annual number of TB cases notified in HCWs in the UK, little evidence of transmission within healthcare settings, with only a few isolated incidents in recent years, exists. 5 In recent decades there has been an expansion, by both the National Health Service (NHS) and private sector healthcare employers, in recruiting HCWs to the UK from abroad, [6][7][8] many of whom originate from high TB incidence countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation